2000
DOI: 10.1016/s1051-0443(07)61331-1
|View full text |Cite
|
Sign up to set email alerts
|

Angioplasty and Stent Placement in Chronic Occlusion of the Superficial Femoral Artery: Technique and Results

Abstract: Abbreviations: ABI ϭ ankle/brachial index, OR ϭ odds ratio, UK ϭ urokinase PURPOSE: To improve the patency rate for angioplasty in chronic occlusion of the superficial femoral artery by deploying stents after angioplasty. MATERIALS AND METHODS:Angioplasty and stent placement were performed in 61 arteries in 48 male patients. The mean occlusion length was 13.5 cm and the mean stent length was 30 cm. Patency rates were analyzed at 6 months and at 1, 2, 3, and 4 years. The predictors of restenosis were analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
40
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 19 publications
9
40
1
1
Order By: Relevance
“…The intraluminal recanalization in the treatment of a femoral occlusion longer than 5 cm is poor (45-55% at 12-24 months) [17][18][19], compared with the vein graft patency of 82% at 1 year [9] or 66-81% at 5 years [19][20][21][22]. The subintimal procedure is therefore preferable.…”
Section: Discussionmentioning
confidence: 99%
“…The intraluminal recanalization in the treatment of a femoral occlusion longer than 5 cm is poor (45-55% at 12-24 months) [17][18][19], compared with the vein graft patency of 82% at 1 year [9] or 66-81% at 5 years [19][20][21][22]. The subintimal procedure is therefore preferable.…”
Section: Discussionmentioning
confidence: 99%
“…However, the 1-year patency rate after PTA is low, particularly in the femoropopliteal artery (FPA), with a mean patency rate of 61%. [1][2][3][4][5] Target lesion revascularization (TLR) is required more frequently in the FPA than for the coronary arteries and hence, transcatheter treatment of the FPA is currently hampered by the high restenosis rate.…”
mentioning
confidence: 99%
“…Other studies have reported the results of bail-out stenting strategies (stenting performed if only angioplasty alone fails) which reveal a mean primary patency rate of 55% at 12 months [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%